Interchange : - Richards, Jack C. (Cambridge University Press, 1990)
Interchange is a multi-level course for adult and young adult learners of English from beginning to high-intermediate level. Designed for low-intermediate learners, Level Two covers a range of contemporary topics using an approach that integrates the teaching of grammar and meaningful communicative practice. Written in American English, Interchange reflects the fact that English is a language of international communication, not limited to any one country, region, or culture. The multi-skills syllabus on which the course is based integrates structural, functional, lexical, phonological, situational, and thematic syllabi. The methodology reflects a communicative approach, with an emphasis on both fluency and accuracy.